Prototype Sistem Otomatisasi Pengendalian Treadmill - Pin Panji Yapinus; Agung Rizki Nugraha Rukmantara (Maranatha University Press, 2018)
Today in the era of globalization, the influence of technology is very important, for we can notice its role in all aspects of human life. Exercise is an important thing to consider for healthy life. Run is the simplest sport option and can be done by almost all circles and layers of society. The problem is, people are too busy so do not have enough free time and free space to go to exercise. Treadmill is the tool used to solve the solution. By using the treadmill, people can exercise to run without having to get out from their house. However, in its use people sometimes have an accident because they do not understand the functions of features on the treadmill. In this research, a prototype of automatic treadmill control system was designed to reduce the accident risk.